Sexually inappropriate behaviour in demented elderly people. Issue 957 (5th July 2005) - Alagiakrishnan, K; Lim, D; Brahim, A; Wong, A; Wood, A; Senthilselvan, A; Chimich, W T; Kagan, L
Abstract : Aim: To determine the prevalence, aetiology, and treatment profile of abnormal sexual behaviour in subjects with dementia in psychogeriatric practices. Methods: A retrospective cross sectional study was conducted in a long term care psychiatry consultation service, community based geriatric psychiatry service, and an inpatient dementia behavioural unit in Edmonton, Canada. Results: Forty one subjects (1.8%) had sexually inappropriate behaviour. Of those cognitively impaired subjects with sexually inappropriate behaviour, 20 (48.8%) were living in nursing homes and the rest, 21 (51.2%) in the community. Of these subjects, 53.7% had vascular dementia, 22% had Alzheimer's, and 9.8% had mild cognitive impairment. History of alcohol misuse and psychosis were reported in 14.6% and 9.8% of subjects respectively. Twenty seven (65.7%) had verbally inappropriate behaviour and 36 (87.8%) had physically inappropriate behaviour. In this study, verbally inappropriate behaviour was more commonly seen in the community sample (81%) than in the nursing home sample (50%) (p = 0.04). Behavioural treatment was also more commonly seen in the community sample (81%) than in the nursing home sample (45%) (p = 0.01). Conclusion: In this study sexually inappropriate behaviour was seen in all stages of dementia, more commonly associated with subjects of vascular aetiology, and is as commonly seen in community dwelling subjects with dementia as in nursing home subjects.